2012
DOI: 10.5539/sar.v2n2p60
|View full text |Cite
|
Sign up to set email alerts
|

Content and Retention of Provitamin A Carotenoids Following Ripening and Local Processing of Four Popular Musa Cultivars from Eastern Democratic Republic of Congo

Abstract: Changes in the concentrations and retention levels of total and individual provitamin A carotenoids (pVACs) during ripening and local processing of the four most popular Musa cultivars of Eastern Democratic Republic of Congo were established through HPLC analysis. The predominant pVACs were all trans β-and α-carotene, together constituting about 90% of total pVACs content in raw and processed Musa fruit pulp. The proportion of β-and α-carotene was not significantly different in the tested East African Highland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 21 publications
4
37
1
Order By: Relevance
“…Studies on in vitro bioaccessibility of provitamin A carotenoids of popular banana cultivars from eastern Africa showed that following processing, the amount of provitamin A carotenoids micellized and ready for absorption was significantly higher in banana-derived dishes (16-27%) than that observed in popular roots and tubers (Ekesa et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on in vitro bioaccessibility of provitamin A carotenoids of popular banana cultivars from eastern Africa showed that following processing, the amount of provitamin A carotenoids micellized and ready for absorption was significantly higher in banana-derived dishes (16-27%) than that observed in popular roots and tubers (Ekesa et al, 2013).…”
mentioning
confidence: 99%
“…Plantain, or cooking banana, has been reported as the second most important source of calories in Eastern Democratic Republic of Congo (DRC), after cassava (Davey et al, 2007;Ekesa et al, 2013). Average annual consumption of cooking banana in Uganda, Rwanda and Burundi is about 250-400 kg (550-880 lb) per person (about 3-11 bananas each day) (Englberger et al, 2003).…”
mentioning
confidence: 99%
“…Additional work by Ekesa et al (2013) showed that the level of pVACs in popular banana cultivars in Eastern Africa ranged from 7 to 27 nmol g -1 DW. Differences in pVACs content in banana fruit have been attributed to genotype-specific differences as well as the differences in the developmental status of the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in pVACs content in banana fruit have been attributed to genotype-specific differences as well as the differences in the developmental status of the fruit. Given that certain banana cultivars that are grown outside Eastern Africa have higher levels of pVACs than local cultivars (Davey et al, 2007;Ekesa et al, 2013;Englberger et al, 2003;Fungo and Pillay, 2011), they can be explored for addressing VAD in the region.…”
Section: Introductionmentioning
confidence: 99%
“…The banana fruit is eaten cooked as a vegetable or ripe as a fruit, and it is also used to produce beer and wine (Rishirumuhirwa, 2010). Besides being a cheap and easily produced source of energy, it is also a good source of vitamins A, C, B6 and minerals, such as potassium (Davey et al, 2007;Ekesa et al, 2013). Rwanda with an annual per capita consumption of 258 kg (Jagwe et al, 2008) and production of 1.8 Mt (FAOSTAT, 2017), ranks among the top banana producers in the world.…”
Section: Introductionmentioning
confidence: 99%